EPIFANI WAJAH DI TENGAH KRISIS RELASI Refleksi Filosofis “Aku” Dengan “Yang Lain” Dalam Konsep Alteritas Emanuel Levinas - Alfredo Kevin (Aggiornamento, 2021)
The Focus of this study is to interpret relations between fellow humans through facial representations in the midst of crisis interaction in a philosophical perspective. The method used in this study is critical reflection based on the review of Emanuel Levinas philosophy of alterity concept. This study is intended as a philosophical reflection on the loss of the essence of a relationship. The phenomenon of corruption cases that occur in Indonesia is an important discourse for humans related to their duty to maintain the sustainability of the lives of others in the world. Not a few humans have suffered from this relationship crisis. Starting from this problem, the author finds that it is necessary to build a relationship that revives a universal sense of humanity and the consequences of what is called substitutional responsibility in the form of ethical death. The irony is that the attitude of helping each other and loving others is slowly being eliminated by selfishness. So, it takes a reconstruction of Emanuel Levina’s mindset in his philosophy of alterity by placing “the other” no longer as number two, but placing in the first place and deserving of protection in the midst of the current disaster